Epidemiological profile of patients hospitalized for thyrotoxicosis between 2013 and 2023 in a Southern Brazil state (Paraná) (Research, Society and Development, 2025)
This study aims to present an analysis of the epidemiological profile of hospitalizations (sex and age group) of patients admitted for thyrotoxicosis in the state of Paraná between 2013 and 2023, with comparisons made to data from the Southern region and from Brazil as a whole over the same period. The data presented are available from the DataSUS online platform of the Brazilian Ministry of Health. In this context, in Paraná, a predominance of hospitalizations among women was observed, with the highest incidence between 30 and 39 years of age, the same age group represented in part of the deaths. In the Southern region, the pattern of hospitalizations was also predominantly female, with emphasis on the same age group; however, deaths were concentrated among women aged 70 to 79 years. At the national level, both hospitalizations and deaths showed a predominance of females, with higher frequency in the 40–49-year age group. The data reveal consistency in the sex profile but regional variations in the most affected age groups. Therefore, further studies are suggested to determine whether these trends will persist over time and to achieve a better understanding of the epidemiology of this endocrinological disorder.